(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of competence and job satisfaction on employee performance at the Regional Secretariat Office of Southeast Sulawesi Province. The study employs a quantitative approach with an associative research design. The population and sample consist of all 100 employees at the Regional Secretariat Office of Southeast Sulawesi Province; consequently, a convenience sample was used. Data were collected via a structured questionnaire designed based on indicators of competence, job satisfaction, and employee performance, and were subsequently analysed using multiple linear regression analysis with the aid of SPSS version 25 software. The results indicate that competence and job satisfaction simultaneously have a positive and significant effect on employee performance. Partially, competence does not have a significant effect on employee performance, whilst job satisfaction has a positive and significant effect on employee performance. These findings suggest that improvements in employee performance are more influenced by levels of job satisfaction than by individual competence; therefore, organisations need to pay greater attention to the factors that shape employee job satisfaction.